Human impact recorded in lake environment (Charzykowskie Lake, N Poland) during the last 6,200 years - Mirosław-Grabowska, Joanna; Zawisza, Edyta; Obremska, Milena; Kowalczyk, Joanna; Zbucki, Łukasz; Tobolski, Kazimierz (Acta Geologica Polonica, 2023)
Based on geochemical and biological investigations of a 6-m-long sediment core, a reconstruction of the environmental conditions in Charzykowskie Lake (northern Poland) is presented. The analyzed sediments consist of fine calcareous detritus gyttja interbedded by lake marl. The results of palynological analysis document the vegetation development around and in the studied lake and confirm the middle and late Holocene age of the sedimentation of the deposits. The identification of 22 taxa of subfossil Cladocera shows the biodiversity of the fauna and reflects the changes in the trophic and water level. The concentrations of various chemical elements suggest the origin of the sediments. Geochemical, including isotope, and biological data, made it possible to reconstruct the environmental conditions, as well as traces of human influence over the last ca. 6,200 years. Four stages of human impact have been documented by the pollen data. The first traces of human groups in the vicinity of Charzykowskie Lake are preserved in sediments from about 4,000 years ago. The human activity is poorly recorded in the Cladocera and in the geochemical compositions of the lake sediments, probably due to the size and depth of the lake and its isolation.
Keywords: Holocene; lake sediments; geochemistry; Subfossil Cladocera; pollen; Humanimpact; N Poland